Penguatan Kemandirian Pangan Nasional Melalui Produk Olahan Jagung di Kecamatan Pajarakan Kabupaten Probolinggo: Strengthening National Food Self-Reliance Through Corn Processed Products in Pajarakan District, Probolinggo Regency - Nadhirah, Aulia; Saadillah, Dinu; Al Ardi, Aditya Nizar; Universitasari, Pascawati Savitri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The agricultural sector can be one of the sectors capable of creating a high number of jobs, but the farmers themselves have the business development of crops into processed products so that they have a high selling value. Most of the farmers in Probolinggo Regency still sell their crops directly without going through further processing, especially for corn. Regulation of the Minister of Agriculture Number: 43/Permentan/OT.140/10/2009, concerning the Movement for the Acceleration of Diversification of Food Consumption (P2KP) Based on Local Resources encourages people to consume diversified non-rice food products, one of which is processed corn products. Therefore, it is necessary to optimize efforts to process corn so as to provide added value to farmers in the form of training to utilize corn yields into innovative and varied new products in order to strengthen food security and increase welfare for farmers. This community service activity was carried out at the Lestari farmer group in Pajarakan District, Probolinggo Regency. The implementation of service activities is in the form of providing training to corn farmers in processing sweet corn into corn chip snacks which have a higher selling value and helping to provide knowledge about online marketing and direct distribution to consumers. The participants gained some knowledge regarding the benefits of added value and also procedures for processing corn into corn chips to add value to a product. Not only did the knowledge increase but the skills of the participants also increased with the training carried out.